Serum Interleukine 35 in Iraqi female patients with newly diagnosed of rheumatoid arthritis. - Al-Tai, Anwar F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Rheumatoid arthritis (RA) characterized by local and systemic effects of inflammation has a wide range of biochemical markers implicated directly or indirectly to its pathogenesis. Patients and method: Serum of (55 Females) of newly diagnosed RA and 23 healthy Females were used to estimate their interlukine levels.Objective: To evaluate interlukine 35 (IL-35) in Iraqi females with newly diagnosed RA and to assess its contribution in the disease process. Results: Females of RA showed a significant increase in the levels of interleukine 35(IL-35) and in the levels of High Sensitivity C-Reactive Protein (hs CRP). While there were no significant changes in the level of alkaline phosphatase (ALP) and calcium (Ca). The correlation between IL-35 and each of hs CRP, ALP and Ca (-ve) were non-significant (r = -0.066, -0.04271 and -0.103) respectively. Conclusion : This is the first study to show the elevation of serum levels of IL-35 in Iraqi female patients with newly diagnosed RA which indicates that IL- 35 may be a good biomarker for early RA.